TWINSPAN CLASSIFICATION OF VEGETATION FROM NORTH EAST ASPECT OF LOWER TANAWAL ABBOTTABAD, PAKISTAN - bibi, Adeela (International Journal of Research -GRANTHAALAYAH, 2022)
The main objective of this research study was to explore the vegetation of Lower Tanawal, Pakistan from North East aspect. The ordination techniques TWINSPAN, DCA and CCA were used to classify the data. TWINSPAN classified 157 plant species and 20 stands into four plant communities. Four plant communities Dodonaea-Ziziphus-Oxalis, Pinus–Olea–Micromeria, Debregessia-Mentha-Isodon, and Pinus-Punica-Isodon community were noted. This study provides first information about the vegetation of Lower Tanawal, Abbottabad Pakistan from North East aspect.